2007
DOI: 10.1109/tgrs.2007.894935
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Model of the Bare Soil Microwave Emission at L-Band

Abstract: A simple reflectivity model of a bare soil at L-band is developed to account for the effects of soil roughness at different angles and polarizations. This model was developed using a long-term dataset acquired over the bare soil in the framework of the Surface Monitoring Of the Soil Reservoir EXperiment (SMOSREX). It is shown that the roughness effects are different depending on the measurement configuration, in terms of incidence angle and polarization. However, in this paper, a simple parameterization that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(71 citation statements)
references
References 21 publications
7
63
0
1
Order By: Relevance
“…R and RMSE were only calculated for grid cells where AMSR-E or AS-CAT and Noah have more than 20 common values. Over extremely dry regions (e.g., Sahara desert), AMSR-E has fewer soil moisture retrievals, possibly due to the constant value of surface roughness used in the VUA-NASA algorithm (Schneeberger et al, 2004;Escorihuela et al, 2007;De Jeu et al, 2009;Liu et al, 2010).…”
Section: Cumulative Distribution Function Matchingmentioning
confidence: 99%
“…R and RMSE were only calculated for grid cells where AMSR-E or AS-CAT and Noah have more than 20 common values. Over extremely dry regions (e.g., Sahara desert), AMSR-E has fewer soil moisture retrievals, possibly due to the constant value of surface roughness used in the VUA-NASA algorithm (Schneeberger et al, 2004;Escorihuela et al, 2007;De Jeu et al, 2009;Liu et al, 2010).…”
Section: Cumulative Distribution Function Matchingmentioning
confidence: 99%
“…Verhoest et al, 2007a;van der Velde et al, 2007;Joseph et al, 2008) and passive (e.g. Escorihuela et al, 2007;Panciera et al, 2009;de Jeu et al, 2009) microwave remote sensing. In this study, effective roughness parameters (s eff and l eff ) are calculated for each (σ 0 , M v )-observation using the single scattering approximation of the IEM (Fung et al, 1992;Fung, 1994).…”
Section: The Effective Roughness Approachmentioning
confidence: 99%
“…Both are functions of the frequency. Recent studies have shown that h s also depends on soil moisture [17]. In order to retrieve soil moisture from the antenna temperature at a single direction, some assumptions are made:…”
Section: Soil Moisture Retrievalmentioning
confidence: 99%